2019
DOI: 10.1039/c8cy02039f
|View full text |Cite
|
Sign up to set email alerts
|

Modification strategies for enhancing the visible light responsive photocatalytic activity of the BiPO4nano-based composite photocatalysts

Abstract: The present issues related to environmental purification have led to a great need for the development of a superior oxidation process to solve the life-threatening problem. The use of the BiPO4 nanomaterial in photocatalysis is one of the best methods for the treatment of wastewater due to its less harmful nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 179 publications
2
15
0
2
Order By: Relevance
“…Studies have shown that nanocrystal graphene has more high-quality photocatalytic potential than many promising nanoparticles under light irradiation. 118,134 The widespread application of nanocrystal graphene has been hampered due to its low separation efficiency of photo-excited electrons and holes. There have been many schemes to overcome these defects, such as forming a heterojunction structure via coupling with other semiconductors, 120,121 doping with non-metals 121,122 and depositing noble metals.…”
Section: Photocatalysismentioning
confidence: 99%
“…Studies have shown that nanocrystal graphene has more high-quality photocatalytic potential than many promising nanoparticles under light irradiation. 118,134 The widespread application of nanocrystal graphene has been hampered due to its low separation efficiency of photo-excited electrons and holes. There have been many schemes to overcome these defects, such as forming a heterojunction structure via coupling with other semiconductors, 120,121 doping with non-metals 121,122 and depositing noble metals.…”
Section: Photocatalysismentioning
confidence: 99%
“…Na fotocatálise, utilizam-se catalisadores, tais como os cristais de BiPO 4 , para a degradação de resíduos orgânicos, o que contribui para a preservação do meio ambiente 6 . Um destes corantes utilizados em indústrias têxteis é o azul de metileno.…”
Section: Introductionunclassified
“…Porém, este material apresenta uma faixa de resposta de luz estreita na região do UV, o que limita a eficiência de transmissão da carga fotoinduzida. Portanto, é necessário encontrar um método eficaz para melhorar o desempenho fotocatalítico e expandir o intervalo de absorção 6 .…”
Section: Introductionunclassified
“…The photocatalytic degradation of organic pollutants in wastewater is an attractive, environmentally friendly and green method that offers a way to harness solar power efficiently and convert them into non-toxic degradation products [1,2,3,4,5,6,7,8]. Recently, although great progress has been made in the field of photocatalysis, only few photocatalysts can effectively use visible light in the degradation of organic pollutions.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth phosphate (BiPO 4 ) as a photocatalyst has been widely studied because of its good photoelectric performance, low cost, low toxicity, excellent photocatalytic activity, and high stability [1]. However, the large optical bandgap ( E g = 4.5 eV) of BiPO 4 limits the transmission efficiency of photon-generated carriers and light-response range to sunlight [17,18].…”
Section: Introductionmentioning
confidence: 99%